Identifying the Research and Trends in STEM Education in Pakistan: A Systematic Literature Review. (August 2022) - Aslam, Sarfraz; Saleem, Atif; Kennedy, Teresa J.; Kumar, Tribhuwan; Parveen, Khalida; Akram, Huma; Zhang, BaoHui
Although STEM is an essential feature of 21st-century education and learning, there is a lack of awareness about it in Pakistan, especially at the K-12 and tertiary levels. Recently many initiatives have been launched across Pakistan to create more interest in STEM education. In order to assist in raising the level of STEM awareness in Pakistan, this study sought to examine the current state of research and identify recent contributions and gaps in the literature. A systematic literature review was conducted using 22 research papers from five renowned databases. Results produced limited research in this area, with the majority being descriptive and only four being interventional studies. Regrettably, no research explored the engineering component of STEM education. Trends indicate that STEM education research has experienced a downward trend in Pakistan. The observed decline may have occurred due to a lack of understanding among Pakistani researchers regarding the importance of STEM education. Additionally, we identified the current gaps in research on STEM education and subsequently provided recommendations for future research.